2002
DOI: 10.1021/ja026488g
|View full text |Cite
|
Sign up to set email alerts
|

A Density Functional Study of O−O Bond Cleavage for a Biomimetic Non-Heme Iron Complex Demonstrating an FeV-Intermediate

Abstract: Density functional theory using the B3LYP hybrid functional has been employed to investigate the reactivity of Fe(TPA) complexes (TPA = tris(2-pyridylmethyl)amine), which are known to catalyze stereospecific hydrocarbon oxidation when H(2)O(2) is used as oxidant. The reaction pathway leading to O-O bond heterolysis in the active catalytic species Fe(III)(TPA)-OOH has been explored, and it is shown that a high-valent iron-oxo intermediate is formed, where an Fe(V) oxidation state is attained, in agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
112
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 37 publications
(74 reference statements)
18
112
1
Order By: Relevance
“…[4] As previously suggested, [1,2,6] it is likely that a high-valent iron-oxo species is formed along the reaction pathway, and our DFT calculations have provided insight into the mechanism of olefin oxidation by the exceptional HOÀFe V = O oxidant. It is possible that epoxidation may also occur by direct attack of the precursor Fe À OOH on the olefin, and a preliminary study in this direction has suggested that such a pathway is slightly disfavored over the competing OÀ O bond cleavage to generate the HOÀFe V = O oxidant.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…[4] As previously suggested, [1,2,6] it is likely that a high-valent iron-oxo species is formed along the reaction pathway, and our DFT calculations have provided insight into the mechanism of olefin oxidation by the exceptional HOÀFe V = O oxidant. It is possible that epoxidation may also occur by direct attack of the precursor Fe À OOH on the olefin, and a preliminary study in this direction has suggested that such a pathway is slightly disfavored over the competing OÀ O bond cleavage to generate the HOÀFe V = O oxidant.…”
supporting
confidence: 67%
“…[6] The three unpaired electrons are mainly distributed on the iron atom (1.58), the oxo oxygen atom (1.0), and the hydroxo oxygen atom (0.44): a spin distribution not unlike that found for compounds I of heme peroxidases and cytochrome P450 and related model complexes. [7,8] The corresponding sextet and doublet states of HOÀFe V =O lie more than 10 kcal mol À1 higher in energy than the quartet ground state.…”
mentioning
confidence: 97%
“…However, in the cis-hydroxylating dioxygenases, the Rieske center can only provide one electron; thus, an Fe III OOOH, Fe V AO, or a redox equivalent species must be invoked in this reaction (37). From the calculations in Table 2 for the non-heme ligand set of PAH, the energetics are reasonable for OOO heterolysis (because of the negatively charged carboxylate and hydroxide ligands), as has recently been calculated for a low-spin Fe III model complex (38). However for the high-spin enzyme case, there is an additional energy barrier (Ϸ10 kcal͞mol), at least for OOO bond homolysis, because of an allowed crossing of energy levels (34).…”
mentioning
confidence: 70%
“…However, we demonstrate that the 607-nm form produces the 804 cm Ϫ1 species and suggest that it arises from a Fe(IV)ϭO/Cu B 3ϩ species. A Fe(V)ϭO/Cu B 2ϩ structure has been proposed for the 804 cm Ϫ1 mode in the CcO/O 2 reaction, and very recently, evidence supporting the ϩ5 valence state in a non-heme Fe has been reported (58). As suggested by Kitagawa and co-workers (59), in the presence of an electron-withdrawing group attached to heme a 3 (formyl), the a 1u and a 2u level could be lower than the d xz and d yz orbitals.…”
Section: Discussionmentioning
confidence: 96%